Predictors of depression among caregivers of disabled children in community based rehabilitation centres in Selangor - Subramaniam, V. C. Anuratha; Baharom, Anisah; Mohd Zulkefli, Nor Afiah (Community Health Society Malaysia, 2017)
Background: Disabled children caregivers face challenges in their daily life as being a caregiver is not an easy task especially towards activities of daily living of dependent children. This study was carried out to determine predictors of depression among caregivers of disabled children. Materials and Methods: A cross-sectional study was conducted among caregivers of disabled children attending Community Based Rehabilitation (CBR) centres in four randomly selected districts in Selangor. Data were obtained using self-administered questionnaire. Depression was screened using DASS-21 questionnaire. All collected data were analysed using IBM Statistical Package for Social Science (SPSS) version 21, involving descriptive and multivariate analysis. Results: Response rate was 81% with a total of 348 respondents. Prevalence of depression was 21% in this study. Predictors for depression were caregivers level of education (AOR = 3.64, 95%CI=1.42-9.30), disabled child attainment of other education (AOR = 2.16, 95%CI= 1.06 - 4.42), financial assistance received (AOR =0.39, 95%CI= 0.29-0.93) and maladaptive coping strategy (AOR = 1.22, 95%CI= 1.13-1.31). Conclusion: This study showed that caregivers education level, coping strategy and financial support play an important role in developing depression. Thus these caregivers need a supportive circle for them to prevent depression in their life which could affect quality of care of their disabled children.